Experimental analysis of new palm oil wax material for engineering application - Ahmad Nabil Mohd Khalil (School of Manufacturing Engineering, Universiti Malaysia Perlis, 2012)
The objectives of this research are to determine the influence on tensile strength and hardness of different composition blends by using design of experiment (full factorial design) and to select the optimum composition blends; to determine the machinability characteristics of three different compositions above based on surface roughness measurement, chips formation, and dimensional accuracy and to determine the optimum percentage composition for the highest tensile strength for the three different compositions.